Individual differences in slow wave sleep architecture relate to variation in white matter microstructure across adulthood - Gudberg, Christel; Stevelink, Remi; Douaud, Gwenaëlle; Wulff, Katharina; Lazari, Alberto; Fleming, Melanie K.; Johansen-Berg, Heidi (Frontiers in Aging Neuroscience, 2022)
Sleep plays a key role in supporting brain function and resilience to brain decline. It is well known that sleep changes substantially with aging and that aging is associated with deterioration of brain structure. In this study, we sought to characterize the relationship between slow wave slope – a key marker of sleep architecture and an indirect proxy of sleep quality - and microstructure of white matter pathways in healthy adults with no sleep complaints. Participants were 12 young (24-27 years) and 12 older (50-79 years) adults. Sleep was assessed with nocturnal electroencephalography (EEG) and the Pittsburgh Sleep Quality Index (PSQI). White matter integrity was assessed using tract-based spatial statistics (TBSS) on tensor-based metrics such as Fractional Anisotropy (FA) and Mean Diffusivity (MD). Global PSQI score did not differ between younger (n=11) and older (n=11) adults (U=50, p=0.505), but EEG revealed that younger adults had a steeper slow wave slope at both frontal electrode sites (F3: U=2, p<0.001, F4: U=4, p<0.001, n=12 younger, 10 older). There were widespread correlations between various diffusion tensor-based metrics of white matter integrity and sleep slow wave slope, over and above effects of age (n=11 younger, 9 older). This was particularly evident for the corpus callosum, corona radiata, superior longitudinal fasciculus, internal and external capsule. This indicates that reduced sleep slow waves may be associated with widespread white matter deterioration. Future studies should investigate whether interventions targeted at improving sleep architecture also impact on decline in white matter microstructure in older adults.